Detection of frictional meltwater on snow surface using a humidity indicator - Shiraz Ahmed Siddiqui; Michael Hasler; Martin Mössner; Joost van Putten; Kurt Schindelwig; Werner Nachbauer (Bern Open Publishing, 2024)
Introduction & Purpose The low friction coefficient of a ski on snow is due to the formation of a meltwater layer between the ski base and the snow surface. It is a widely accepted theory that the formation of this meltwater is due to frictional heating (Bowden & Hughes, 1939). The experimental evidence regarding the formation of frictional meltwater has been a challenging task. This is because meltwater is dynamically created and most likely refreezing immediately once the frictional heat input is terminated. Ambach & Mayr (1981) measured the change in capacitance of a probe to quantify the thickness of the meltwater layer. They reported a thickness of the meltwater layer of 4-20 µm during downhill skiing with sliding speeds up to 17 m/s and ambient temperatures of -5 °C and -10 °C. The reported thickness was put into question by Colbeck (1994). Strausky et al. (1998) used fluorescence spectroscopy to detect the meltwater layer. However, they concluded to have observed no water layer above their detection limit of 0.05 µm at speeds up to 0.1 m/s (an unrealistic speed of skiing). Hasler et al. (2021) used infrared imaging at a snow temperature of -4 °C, and gave evidence regarding meltwater formation by observing the temperature change of the snow surface after the ski passage. Furthermore, heat dissipation calculations made by Colbeck (1988), numerical modelling by Bäurle et al. (2007) and Makkonen & Tikanmäki (2014) suggest the thickness of the meltwater layer to be below 1 µm. Despite decades of research in the field of ski-snow tribology, the conclusive evidence regarding the formation of this meltwater layer and its detection are contentious. The complexity of the task of frictional meltwater detection is due to several influencing factors like small contact spots, low water layer thickness, short time intervals, high sliding speed of ski etc. In this regard, our purpose is to present an innovative approach for detecting the formation of frictional meltwater by applying a humidity indicator to the surface of snow and analysing the change in its color in response to contact with water. Methods Humidity indicators are chemicals that change their color in response to contact with water. As a humidity indicator we use crystal violet which is widely used as a dye in textile industry and for printers. The mechanism of color change of crystal violet involves a chemical reaction, resulting in the formation of a covalent bond between the central carbon atom and a hydroxyl ion (OH-). During ski-snow interaction, if the frictional heat generates a meltwater layer, the formed hydroxyl ions should undergo a direct chemical reaction with crystal violet resulting in a permanent color change of the chemical. The resulting change in color of the chemical from violet to blue is supposed to be a good indicator of the formation of frictional meltwater. The experiments were performed at the snow lab of the Research Center Snow, Ski and Alpine Sports at the University of Innsbruck (Austria) on a linear tribometer with 18 m sliding surface length (Hasler et al., 2016). A cross-country ski (Salomon LAB WC Equipe 10 Skate, 192 cm) was moved at a sliding speed of 15 m/s. The normal load was 430 N taking into account half the weight of the skier during XC skiing. On three different days we performed experiments with different snow temperatures. First day with snow temperature -1 °C, the next day with -3 °C and then on the third day with -5 °C. On each day, the gliding experiment was repeated on four snow tracks. The reason to select this range of temperatures was that we expected more frictional meltwater at higher temperatures. Crystal violet was sprayed over the snow surface using a pump sprayer. After spraying the chemical, a 30-minute break was applied to allow for any reaction with the surface. However, no change in the color of the chemical was observed. A digital camcorder (Sony FDR-AX53, video resolution 1920 x 1080, with frame rate of 50 Hz) was mounted close to the snow track to record the entire measurements. There was a manual white balance done before the start of video recording. During the entire measurements, there was no change in the camera settings and the lighting conditions did not change. Regular monitoring of the snow temperature was done using a PT1000 sensor (Nexensos W-EYK, Heraeus Holding GmbH, Germany) and an 18-bit data logger (Datataker DT80, ThermoFisher Scientific, United States). After the test, the images captured before, and after the runs were systematically analysed using a self-developed program in LABVIEW (National Instruments Corporation, Austin, Texas, USA). The objective was to detect meltwater caused by the frictional heating through the passage of the ski. With the presence of meltwater, crystal violet changes its color from violet to blue. To evaluate the color change, we separated the images into the three-color channels red, green and blue and calculated the intensity ratio red/blue. The decrease in the ratio indicates the presence of meltwater. For numerical evaluation of the data, we took a percentage change of the average ratios in the frames and then calculated the average for all ten runs. Results We observed a decrease in the red/blue ratio between the two images captured before and after the ski passage indicating the presence of more blue pixels. At snow temperature -1 °C, the average of the percentage decrease in ratio (red/blue) is -6.37% which is the highest as compared to -3.47% (at -3 °C) and -0.66% (at -5 °C). This shows that there is more pronounced color change at -1 °C, which gives an indication that the amount of frictional meltwater formed is highest at this temperature. Discussion The experimental results using the humidity indicator gave evidence for the generation of frictional meltwater. The frictional heat leads very probably to the formation of meltwater which in turn reacts with the crystal violet and changes its color. The change in color of the chemical from violet to blue was most pronounced at -1 °C (close to the melting point) as compared to lower temperatures (-3 °C and -5 °C). At constant frictional heat production, we expect most frictional meltwater at -1 °C because of the energy required is lowest to raise the snow temperature from -1 °C to the melting point of snow at 0 °C as compared to the other temperatures. The response of crystal violet in contact with the formed meltwater provides good evidence for unravelling and further understanding the mechanisms of ski-snow friction. This approach is useful for detecting the presence of meltwater but the amount or the thickness of the layer cannot be determined. Hence, the analysis is semiquantitative and requires more precise techniques like thermal imaging or measuring the dielectric properties of snow. Conclusion The goal of this work to detect the frictional meltwater using a humidity indicator was successfully achieved. These are the novel results providing experimental evidence of frictional meltwater. The present work provides a good basis to compare the amount of frictional meltwater formed at the three examined snow temperatures. Acknowledgement This work was supported by the Austrian Science Fund (FWF): [P36489-N]. References Ambach, W., & Mayr, B. (1981). Ski gliding and water film. Cold Regions Science and Technology, 5(1), 59-65. https://doi.org/10.1016/0165232X(81)90040-9 Bäurle, L., Kaempfer, T. U., Szabó, D., & Spencer, N. D. (2007). Sliding friction of polyethylene on snow and ice: Contact area and modeling. Cold Regions Science and Technology, 47(3), 276-289. https://doi.org/10.1016/j.coldregions.2006.10.005 Bowden, F. P., & Hughes, T. (1939). The mechanism of sliding on ice and snow. Proceedings of the Royal Society A. Mathematical and Physical Sciences, 172(949), 280-298. https://doi.org/10.1098/rspa.1939.0104 Colbeck, S.C. (1988). The kinetic friction of snow. Journal of Glaciology, 34(116),78-86. https://doi.org/10.1017/S0022143000009096 Colbeck, S.C. (1994). A review of the friction of snow skis. Journal of Sports Sciences, 12(3), 285-295. https://doi.org/10.1080/02640419408732174 Hasler, M., Jud, W., & Nachbauer, W. (2021). Snow temperature behind sliding skis as an indicator for frictional meltwater. Frontiers in Mechanical Engineering, 7, Article 738266.